Chapter 6 Textures of urban fears The affective geopolitics of the 'oriental rug' - Bialasiewicz, Luiza (Taylor & Francis, 2020)
We will discuss in detail the two exhibitions and their vicissitudes in the paragraphs to come, focusing on the emotional public reactions they both evoked, albeit to different degrees.